2000
DOI: 10.1515/jpem.2000.13.2.179
|View full text |Cite
|
Sign up to set email alerts
|

Iron Deposition in the Anterior Pituitary in Homozygous Beta-Thalassemia: MRI Evaluation and Correlation with Gonadal Function

Abstract: MRI in conjunction with a GnRH stimulation test may be useful in predicting future impairment of pituitary function; however, further studies are needed to assess the effect of chelation therapy on the iron overload in the gland.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 11 publications
2
36
0
1
Order By: Relevance
“…Moreover, a pituitary secretory defect in b-thal was previously suggested by demonstrating iron deposition in the anterior pituitary in correlation with gonadal function [18]. Our findings suggest that up to one quarter of adult b-thal patients are GH deficient.…”
Section: Discussionsupporting
confidence: 68%
“…Moreover, a pituitary secretory defect in b-thal was previously suggested by demonstrating iron deposition in the anterior pituitary in correlation with gonadal function [18]. Our findings suggest that up to one quarter of adult b-thal patients are GH deficient.…”
Section: Discussionsupporting
confidence: 68%
“…Hypothyroidism, hypoparathyroidism, diabetes mellitus, and mainly hypogonadism (as delayed puberty and/or secondary hypogonadism) are considered as major causes of osteopenia/osteoporosis in TM (2-4, 6). Hemosiderosis of the pituitary gonadotrophic cells and iron deposition in the testes and ovaries are involved in the pathogenesis of endocrine complications in TM (27). Hypogonadism is a well-recognized cause of osteoporosis and osteopenia not only in patients with TM but also in the general population and is characterized by high bone turnover with enhanced resorptive phase (28).…”
Section: Acquired Factorsmentioning
confidence: 99%
“…7,10 Furthermore, increased R2 and decreased pituitary height have been shown to predict clinical and biochemical HH in adults with thalassemia major. 6,7,11 There has also been evidence that increased R2 precedes pituitary volume loss and hypogonadism. 12 We have demonstrated that R2 deposition can be seen in children as young as 4 years of age, with volume loss beginning in the second decade of life.…”
mentioning
confidence: 99%